Determinants of Accounting Students' Interest in Pursuing a Public Accountant Career - Nugraha, Geonardo Primaditya; Wulandari, Putu Prima (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to obtain empirical evidence regarding the determinants of accounting students' interest in pursuing a career as a public accountant. The research method used is a quantitative approach. The population of the study consists of undergraduate students from the Accounting Department, Faculty of Economics and Business, Universitas Brawijaya, with a total sample of 100 respondents. Data were collected through an online questionnaire distributed via Google Forms. The statistical tool used for data analysis is Partial Least Square (PLS) using the Smart PLS version 4 application. The analysis components include validity tests, such as convergent and discriminant validity tests, reliability tests, and hypothesis testing to determine t-statistics, p-values, and path coefficients using the bootstrapping method. The results of the study show that labor market considerations and academic abilities do not significantly influence accounting students' interest in pursuing a career as a public accountant, while family environment and social values have a positive and significant influence on accounting students' interest in pursuing a career as a public accountant.